Culture and value : tourism, heritage, and property - Bendix, Regina (Indiana University Press, 2018)
When heritage becomes a commodity, when culture is instrumental in driving tourism, and when individuals assert ownership over either, social, ideological, political, and economic motivations intertwine. Bestowing value on "culture" is itself a culturally rooted act, and the essays gathered in Culture and Value focus on the motivations and value regimes people in particular times and contexts have generated to enhance the visibility and prestige of cultural practices, narratives, and artifacts. This collection of essays by noted folklorist Regina F. Bendix, offers a personal record of the unfolding scholarly debate regarding value in the studies of tourism, heritage, and cultural property. Written over the course of several decades, Bendix's case studies and theoretical contributions chronicle the growing and transforming ways in which ethnographic scholarship has observed social actors generating value when carrying culture to market, enhancing value in inventing protective and restorative regimes for culture, and securing the potential for both in devising property rights. Bendix's work makes a case for a reflexive awareness of the changing scholarly paradigms that inform scholars' research contributions.